O ensino de dança na perspectiva da educação física: limites e possibilidades para o ensino médio integrado no Instituto Federal de Educação, Ciência e Tecnologia da Bahia - Nogueira, Samile Guimarães (2022)
This present work is the result of a question that was raised during my years of teaching profession in Physical Education: Questioned how can dance be pedagogically approached in IFBA from the perspective of a critical and Human Integral Formation? It was made a documentary research, from a qualitative and quantitative analysis guided by the main objective of bulding a proposal of teaching dance under a historical perspective in the context of Professional and Technological Education and by the specific objectives of identifying dance, as a teaching know, in the oficial documents that guide the pedagogical practice for Physical Education teaching in the various Campi of IFBA, inside the Technical Courses integrated to High School level; to map studies and registers of practices that contemplate dance teaching in IFBA; to elaborate a proposal for dance teaching, based in Historical-Critical Pedagogy, in the Professional and Technological Education context. It was used as primary data source the 46 Physical Education Planning, constitutive part of the PPC, IFBA oficial documents and, as secondary source, 3 thesis and dissertations produced between 2010 and 2018 which discuss the curriculum of `Physical Education in IFBA and/or dance teaching in the institution. In only 27 (twenty-seven) out of 46 (forty-six) PPC, analysed, dance is seen as a know treated pedagogically by Curricular Component of Physical Education. Dance is, ultimately, a result of the necessity of human communication and, at the same time, the human capacity of communicating, expressing itself. It is language per se. It is constituted by time, space and moviment relation, translating feelings, sensations, perceptions of yourself and the world through gestures. Therefore, we consider its importance in the formative process which intends to be Integral, Critical and Criative. In triangulating the data of the dissemination networks, the analysed researches and the documentary data, we noticed that the oficial documents do not match what the researches point out about the pedagogical practices we stablished, the teaching practices seem contemplate dance more than what the oficial documents show. At the same time, on a contraditory way, we identified a correlation between the markable presence of Physical Education female teachers in the events oficially published by Campi and the theorical quality and contextualization of Dance in the PPC of these Campi. It indicates a possible relation with the female teachers practice in these spaces both in guarantee of the dance in the PPC and seing it out of classrroom, on a artistica perspective. About the proposal of dance teaching, we conclude that the Historical and Critical Pedagogy is a strong point of view about assuming the reality reading, including themes such as Race, Genre and Class, and also that articulating these debates is the only way to promote an education in a liberator perspective beyond capital.